2014
DOI: 10.2166/wh.2014.157
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of corrosion and scaling tendency indices in a drinking water distribution system: a case study of Bandar Abbas city, Iran

Abstract: Corrosion and scaling is a major problem in water distribution systems, thus evaluation of water corrosivity properties is a routine test in water networks. To evaluate water stability in the Bandar Abbas water distribution system, the network was divided into 15 clusters and 45 samples were taken. Langelier, Ryznar, Puckorius, Larson-Skold (LS) and Aggressive indices were determined and compared to the marble test. The mean parameters included were pH (7.8 ± 0.1), electrical conductivity (1,083.9 ± 108.7 μS/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The most frequently used methods for determining the extent of these two processes are Langelier saturation index (LI), Ryznar index (RI), aggressive index (AI), Puckorius index (PI) and Larson-Skold index (LS). These methods are used by many researchers in the different parts of the world [3][4][5][6][7]. Application of geographical information systems (GIS) provides spatial mapping, which gained immense popularity among the other data interpretation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently used methods for determining the extent of these two processes are Langelier saturation index (LI), Ryznar index (RI), aggressive index (AI), Puckorius index (PI) and Larson-Skold index (LS). These methods are used by many researchers in the different parts of the world [3][4][5][6][7]. Application of geographical information systems (GIS) provides spatial mapping, which gained immense popularity among the other data interpretation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, an isotherm demonstrates the relationship between phenol concentration of the solution and amount of the phenol adsorbed by solid phase when the two phases are in equilibrium state. The Freundlich isotherm is an experimental relationship based on adsorption on heterogeneous surfaces and unlike the Langmuir model, does not specify the maximum adsorption capacity and thus, is applicable only at medium or low concentrations (4951). The isotherms are shown in Figures 5 and 6 for both models on the basis of experimental data and parameters resulted from nonlinear regression.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the mean of Puckorius index was 5. (19). According to the study of Mahvi on the water reservoirs in Bandar Abbas city, it was found that 50% and 100% of the water samples were corrosive based on Langelier and Ryznar indices (22).…”
Section: Iran J Health Sci 2017; 5(2): 16mentioning
confidence: 99%
“…The physical factors affecting the corrosion include water velocity, existence of air bubbles, and sand in the water (1,18,19). Chemical agents include low pH, high carbon dioxide, lack of hardness and alkalinity, temperature, total dissolved solids, the concentration of dissolved oxygen, residual chlorine, chloride, sulfate, and other compounds (10, 19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation